The protective effect of taurine against liver disorder induced by gentamicin in male rats - Saad Kahyoon, Orass; H. Flayyih, Salam; G, Al-Fartosi, Khalid (University of Thi-Qar Journal of Science, 2019)
The present study was carried out to investigate the effects of an amino acid taurine on gentamicin-induced liver disorder in male rats. Twenty four male rats were used in this study, the animals divided into four groups, each group contained six rats including: G1 normal group, G2 injection IP with 100mg/kg of gentamicin only for 10 days, G3 injection IP with 100mg/kg of taurine only for 10 days, G4 injection IP with 100mg/kg of gentamicin and injection IP with 100mg/kg of taurine for 10 days, The result shows significant increase (p<0.05) in liver enzymes ALT, AST, ALP and significant increase in TC, TG, LDL with marked decrease in HDL levels in gentamicin group compared with normal group. This animal study suggests that the treatment with gentamicin plus taurine protects against gentamicin-induced acute liver injury by a significant (p<0.05) and improvement in the biochemical markers of liver and normalized lipid profiles.